Driving mechanisms for decoupling CO2 emissions from economic development in the ten largest emission countries. Issue 1 (31st December 2022) - Chen, Chunci; Lu, Yonglong; He, Guizhen
ABSTRACT: The significant contribution to CO2 emissions includes historically cumulative emissions in the United States, Russia, Japan, South Korea, and Germany, as well as the current increase in emerging economies, such as China, India, Iran, Indonesia, and Saudi Arabia, which contribute 68% of global emissions. Therefore, it is important to measure changes in CO2 emissions and driving mechanisms in these countries. This study used the LMDI and STIRPAT model to explore driving mechanisms for decoupling CO2 emissions from economic growth in the 10 largest emission countries based on the World Bank and International Energy Agency databases. The results showed that CO2 emissions have tripled in these countries over the last 55 years, driven primarily by economic growth (+170%) and population growth (+41%), whereas a decline in energy intensity (−87%) and carbon intensity (−24%) slowed the growth of CO2 emissions over most of the period. In China, the United States, and India, significant increases in CO2 emissions were associated with population and economic growth. Intensity effects were prominent in emission reductions in China, the United States, Germany, Japan, and Russia. Overall, the developed countries except for South Korea showed strong decoupling relationships, whereas six developing countries were weak in decoupling.